Complement in Metastasis: A Comp in the Camp - Ajona, Daniel; Ortiz-Espinosa, Sergio; Pio, Ruben; Lecanda, Fernando (Frontiers in Immunology, 2019)
The complement system represents a pillar of the innate immune response. This system, critical for host defense against pathogens, encompasses more than 50 soluble and membrane-bound proteins. Emerging evidence underscores its clinical relevance in tumor progression and its role in metastasis, one of the hallmarks of cancer. The multistep process of metastasis entails the acquisition of advantageous functions required for the formation of secondary tumors. Thus, targeting components of the complement system could impact not only on tumor initiation but also on several crucial steps along tumor dissemination. This novel vulnerability could be concomitantly exploited with current strategies overcoming tumor-mediated immunosuppression to provide a substantial clinical benefit in the treatment of metastatic disease. In this review, we offer a tour d´horizon on recent advances in this area and their prospective potential for cancer treatment.